RECENT DEVELOPMENTS IN REGULATORY MATTERS ON HERBAL MEDICINAL PRODUCTS (HMPS) - Vlietinck, A. J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Within the group of herbal or botanical products there is a large variation with regard to the properties and the legal status worldwide of these products. Some herbal products come closer to or are medicines, while others are close or even identical to foods such as dietary supplements, functional foods, novel foods etc. And still others are considered as cosmetics or medical devices. It is therefore not surprising that recently appropiate regulatory actions have been undertaken to regulate and harmonize the legal status of these various groups of plant preparations throughout the different Western countries. The European Union has recently considered herbal products in several legislative texts. Medicinal use has been harmonized through the Traditional Medicinal Products Directive (Directive 2004/27/EC amending Directive 2001/83/EC as regards THMPs). Use of herbal preparations in unit dose form under law is covered in the Food Supplements Directive (FSD) 2002/46/EC. Regulations on nutritional and health claims and the addition of vitamins and minerals and certain other substances to foods were adopted on October 12, 2006 (Directive 2006/80E/02 and 03). Nevertheless, the distinction between traditional herbal medicinal products and food supplements containing herbal products without nutritional value but having physiological effects remain vague and controversial. In this lecture the implementation of the current European regulations at the level of the EU Member State authorities and manufacturers in terms of quality, safety and efficacy of these herbal products will be discussed. A comparison will be made with other existing concepts worldwide, taking into account not only the abovementioned properties, but also aspects such as access to the market, cost prize and prospects for innovation of herbal products.